Evaluating the anti-icing performance of Hydronic Heating system in pedestrian pavement - Ali, Aboobakkar Nakeeb; Salian, Mokshith Yadava (My University, 2024)
This thesis explores the performance and feasibility of using Hydronic Heating Pavement (HHP) systems for anti-icing and solar energy harvesting on pedestrian pathways and roadways. Two test sites were selected for analysis: the E18 motorway in Östersund and a pedestrian pathway in Gothenburg. The study employed numerical modeling using COMSOL Multiphysics 6.2 to simulate surface temperatures and assess energy requirements. Data including air temperature, dew point, wind speed, precipitation, and radiation were collected from local sources and used to validate the models. The numerical simulations demonstrated that, without heating, the road surface in Östersund experienced up to 2,121 hours of slippery conditions annually, whereas the installation of heating pipes reduced this to 332 hours in Gothenburg’s pedestrian pathway. The annual energy required for anti-icing the pedestrian pathways was calculated to be 62.4 kWh/m²/year, with a mean heat flow of 481.3 W/m from a single pipe. Sensitivity analysis revealed that factors such as pipe distance, thermal conductivity, and fluid temperature significantly impacted system performance. For instance, increasing the pipe spacing doubled the number of slippery hours, while higher thermal conductivity and absorptivity reduced them. Comparisons between roads and pedestrian pathways showed that pedestrian pathways required significantly less energy (seven times lower) due to their narrower width. The results indicate that solar energy harvesting alone is more than sufficient to meet the system’s energy requirements, providing up to five times the total annual energy needed when optimized during the summer months. This study concludes that the hydronic heating pavement system demonstrates significant potential in enhancing safety and minimizing icy conditions on pedestrian pathways. Furthermore, the renewable solar energy harvested is capable of fully supporting the operation of HHP system without any additional inputs.
Keywords: Anti-icing, Heat loss, Ice-free road, Required energy, Hydronic pavement, Heating pavement, Embedded pipes